Perencanaan Dan Perancangan Hotel Dengan Tema Arsitektur Neo Vernakular - Sova Andila; Neneng Yulia Barky (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
On the 21st PON (National Sports Week) show, Indonesia was appointed as the host after several years, based on a Decree (SK) determination by the Minister of Youth and Sports (Menpora) Zainuddin Amali, North Sumatra Province as the host, which is in the Village Sena, Batang Quiz District, Deli Serdang Regency. In the sports center area, supporting infrastructure and commercial areas, namely hotels, are also provided. The depiction of the hotel design applies a neo vernacular architectural theme. The method used in this research is data collection, literature study and analysis and concepts. The analysis carried out is in the form of site analysis, building analysis, structural analysis and utility analysis, from the results of the analysis carried out it can be concluded that the concept obtained for designing the hotel. The application of this building theme can be seen based on the shape, facade, and materials as outlined in the final design in the form of working drawings and 3D designs.